The relationship between Hypertension and weight status in Iraqi population (Baghdad Science Journal, 2011)
Most medical books and researches documented that increased body weight is a predisposing factor to hypertension , and there is recent work in this field as well. In this research , the relationships between hypertension and body weight with age were studied in Iraqi population . It is concluded that diastolic hypertension is separated from systolic and combined hypertension and increased body weight has little effect on increased blood pressure.